Uterine malformations and pregnancy: about 11 cases seen university hospital center of gynecology- obstetric Befelatanana Antananarivo Madagascar - Housni, Ibrahim; Tanjona, Ratsiatosika A.; Rakotonirina, Martial A.; Romuald, Randriamahavonjy; Fleurian, Sidy; Halissiot, Bacar A.; Rokotovao, Hery A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Birth defects in the uterus result from abnormal fusion of the miler ducts and / or failure. Uterine malformations are a common cause of infertility, but if pregnancy occurs absorption from the septum. They are relatively frequent and concern 0.1-3% of the female population, such a situation is potentially high risk obstetric. We report here, 11 cases of uterine malformations during pregnancy seen at the CHUGOB from May 01, 2017 to May 01, 2018. We observed 11 cases of uterine malformations during pregnancy, including 3 cases of didelphus uterus, 3 cases of pseudo-unicornuate uterus, 3 cases of bicornuate uterus, 1 case of septate uterus and 1 case of true unicornuate uterus. The age of the parturients ranged from 22 to 26 with a mean of 23.63 years. Regarding pregnancy, 5 women were primigest, 4 were paucigest and 2 were multiparous. For gestational age, 09 cases came to term and 2 cases pregnancy stopped at 17 weeks. The average birth weight was 2215g. The diagnosis of the malformation was made before the caesarean section in 2 out of 10 cases. Eight out of 10 cases of the fetuses were alive. Congenital uterine malformations are often asymptomatic. The occurrence of pregnancy in a malformed uterus is a rare but potentially serious situation. The diagnosis of these abnormalities is based on new advanced imaging means such as 3D ultrasound.